2020
DOI: 10.1177/1060028020943542
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immune Globulin (IVIG) for Treatment of Autoimmune Heparin-Induced Thrombocytopenia: A Systematic Review

Abstract: Objective: To evaluate intravenous immune globulin (IVIG) for autoimmune heparin-induced thrombocytopenia (aHIT), including platelet recovery, IVIG dose, dosing weight, IVIG product used, and complications reported. Data Sources: PubMed and EMBASE were searched from inception through June 21, 2020. Search terms included heparin-induced thrombocytopenia, HIT, intravenous immune globulin, IVIG, autoimmune HIT, aHIT, and immune globulin. Study Selection and Data Extraction: Patients administered IVIG for HIT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 73 publications
1
23
0
1
Order By: Relevance
“…
bination of APTT reagent and analyzer, 1,3,10 but also by the anti-Xa reagent used for calculation. 1 In conclusion, taken together, our results 1,5 and the data reported by Kovacs et al 2 clearly highlight the urgent need for a better standardization of the anti-Xa assay and particularly the development of better standardized calibration materials.
…”
supporting
confidence: 68%
See 2 more Smart Citations
“…
bination of APTT reagent and analyzer, 1,3,10 but also by the anti-Xa reagent used for calculation. 1 In conclusion, taken together, our results 1,5 and the data reported by Kovacs et al 2 clearly highlight the urgent need for a better standardization of the anti-Xa assay and particularly the development of better standardized calibration materials.
…”
supporting
confidence: 68%
“…However, some aHIT cases required a higher cumulative IVIG dose following lower-than-expected or transient results. [5][6][7] Possible variable inhibitory effect of different IVIG products, polymorphisms in the FcɣIIa receptors, and use of ideal body weight for dose calculation could be explanations for variable effects. 5 Caution is advised regarding a possible variable response after the recommended IVIG regimen in treatment for aHIT and thus, possibly for VITT.…”
Section: Successful Treatment Of Vaccine-induced Prothrombotic Immune Thrombocytopenia (Vipit): Comment From Roberge Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Italian Society for the Study of Haemostasis and Thrombosis (SISET) position statement [ 7 ] and the evolving international recommendations [ 1 ], the severity of the thrombocytopenia at presentation (< 50 × 10 9 /L) imposed the immediate initiation of IVIG [ 8 ] and dexamethasone, as a means of interrupting VITT antibody-induced platelet activation. Conversely, the absence of worsening intracranial hemorrhage allowed us not to consider platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that intact IgG fragments inhibit platelet activation by antibodies. 13 It is important to note that IVIG exhibits prothrombotic effects and may exacerbate symptoms and increase morbidity in a patient presenting with existing blood clots. The patient was also initially started on dexamethasone since TTP was a differential diagnosis.…”
Section: Case Reportmentioning
confidence: 99%